2014
DOI: 10.1016/j.neuroscience.2014.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates brain injury induced by systemic lipopolysaccharide in neonatal rats

Abstract: Our previous study showed that lipopolysaccharide (LPS)-induced brain injury in the neonatal rat is associated with nitrosative and oxidative stress. The present study was conducted to examine whether melatonin, an endogenous molecule with antioxidant properties, reduces systemic LPS-induced nitrosative and oxidative damage in the neonatal rat brain. Intraperitoneal (i.p.) injection of LPS (2 mg/kg) was administered to Sprague–Dawley rat pups on postnatal day 5 (P5), and i.p. administration of melatonin (20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
6
27
0
Order By: Relevance
“…A modulating effect of melatonin on microglia activation was also recently reported in PND5 rats receiving i.p. LPS . In addition, in keeping with our data, a protective effect of melatonin associated with a reduced iNOS activity was recently reported in heart mitochondrial impairment during sepsis .…”
Section: Discussionsupporting
confidence: 93%
“…A modulating effect of melatonin on microglia activation was also recently reported in PND5 rats receiving i.p. LPS . In addition, in keeping with our data, a protective effect of melatonin associated with a reduced iNOS activity was recently reported in heart mitochondrial impairment during sepsis .…”
Section: Discussionsupporting
confidence: 93%
“…Although no changes in Iba‐1(+) area were detected in LPS‐injected optic nerves, melatonin decreased phagocytic microglial activation (as shown by a decrease in ED‐1 immunoreactivity) induced by experimental ON. In agreement with these results, it has been demonstrated that melatonin restrains the activation of microglia following traumatic brain injury , and attenuates LPS‐induced increase in microglial reactivity in the neonatal rat brain . Besides microglia, it has been shown that astrocyte responses contribute to EAE‐ON pathology .…”
Section: Discussionsupporting
confidence: 69%
“…Recently, it was revealed that melatonin decreased iNOS expression and proinflammatory cytokines (TNF‐α and IL‐6), iNOS, and cyclooxygenase (COX)‐2 in sciatic nerves in rats with DM 29 , 38 . Liu et al also demonstrated that melatonin ameliorated the elevated TNF‐α, IL‐1β, IL‐6, iNOS, and COX‐2 levels and decreased the apoptotic cells in hypoxic rats 39 .…”
Section: Discussionmentioning
confidence: 99%